Peculiarities of the Experimental Study of the Pedagogical Culture Formation of the Ground Forces Future Officers in the Process of Humanitarian Disciplines Studying - Viacheslav Sevruk (Pedagogical Discourse, 2022)
The article is devoted to awareness of the important role of humanitarian education in the professional training of future representatives of the officer corps of the Armed Forces. To analyze the changes that may occur during an experimental study, the basic requirements for organizing and adhering to clearly defined stages of the pedagogical experiment were taken into account: organizational, diagnostic, formative, and results-analytical. Humanitarian education in all educational institutions is traditionally carried out in the process of studying humanitarian disciplines. Humanitarian training of future officers is a component of professional training of officer personnel in the system of higher educational institutions.Among the fundamental milestones of the humanitarian development of the Armed Forces, which must be taken into account in the humanitarian training of future officers, the affirmation of the personality of a serviceman as the highest social value is outlined.An important aspect of the professional activity of future officers is to take into account the educational and educational influences in working with subordinates, therefore, graduates of VVNIZ need to take into account the subjectivity of each of the participants in such interaction (character, individual characteristics of each of them, etc.).Future officers are called to demonstrate a high level of pedagogical culture in providing the necessary assistance to subordinates in getting out of crisis situations caused by changes in the life cycle, separation from family, friends, changes in the social situation and social status.The formation of future officers' ability to preserve and multiply moral, cultural, and scientific values ​​involves familiarizing cadets with the laws of development of psychological and pedagogical science as one of the components of the content of humanitarian disciplines. An important aspect in the formation of pedagogical culture in the process of studying humanitarian disciplines is taking into account the content of military professional competencies of future officers. Future officers not only develop knowledge of humanitarian disciplines, abilities and skills related to the manifestation of pedagogical culture, but also try out, choose and assimilate new effective models of interpersonal service-professional interaction in the military team based on the analysis and evaluation of the activities of all participants in the interactions, reflection, aspirations to improve one's own model of activity at a high level of pedagogical culture.